Investigating the Mechanism of Action of Antitumour Benzoprims - Hatfield, Amelia (2024)
KRAS is one of the most frequently mutated oncogenes, with activating mutations occurring in ~ 20% of all human cancers, including >90% of pancreatic cancer, ~40% of colorectal cancer (CRC) and ~30% of non-small cell lung cancer (NSCLC). Until recently, KRAS inhibitors have not been successful clinically despite years of effort, mainly due to RAS proteins not appearing to possess suitable binding pockets to which small molecule inhibitors can bind. However, in 2021, the first KRASG12C inhibitor was approved for clinical use - Sotorasib®.